Hospitalisation in Patients With Heart Failure With Preserved Ejection Fraction. Issue 12 (6th January 2018) - Nanayakkara, Shane; Patel, Hitesh C; Kaye, David M
Heart failure is highly prevalent with more than 50% of cases being patients with a preserved ejection fraction (HFPEF), a figure that is projected to increase due to the changing risk factor landscape, in particular the ageing population. Overall mortality is similar to patients with heart failure with reduced ejection fraction (HFREF), as are the rates of hospitalisation. Patients with HFPEF have more comorbid conditions with fewer therapeutic options available. In this review, we explore the epidemiology of hospitalisation of HFPEF, the impact of current treatment modalities, and the potential of future therapies.